Jacqueline Vansant. Austria Made in Hollywood. Camden House, 2019. - Jason Doerre (Studies in 20th & 21st Century Literature, 2022)
Review of Jacqueline Vansant. Austria Made in Hollywood. Camden House, 2019. 196 pp.
Keywords: Austria; film; Hollywood; film studies